Suggested physical education activities for educable mentally retarded children (primary level) - Evangelista, Benilda R. (College of Education, University of the Philippines Diliman, 1970)
Realizing the importance of physical education in the life of the retarded children, the study was made in an effort to adapt the activities to meet the needs of the retarded child in a physical education class. The information and data presented in the study were mainly gathered from the readings and library research conducted. The researcher found out that through physical education activities, the special education teacher can help a retarded child develop in all areas - physically, because all physical education activities require movement; mentally, because players must remember some rules and routines and be alert for a turn; socially, because the very word "play activities" indicates an association of two or more people; and emotionally, because a player is accepted by other people for what he is and at the same he has enjoys it.